Regulating decentralized systems: Evidence from sanctions on Tornado Cash - Anders Brownworth; Jon Durfee; Michael Junho Lee; Antoine Martin (Federal Reserve Bank of New York, 2024)
Blockchain-based systems are run by a decentralized network of participants and are designed to be censorship-resistant. We use sanctions imposed by the U.S. Department of Treasury on Tornado Cash (TC), a smart contract protocol, to study the impact and effectiveness of regulation in decentralized systems. We document an immediate and lasting impact on TC following the sanction announcement, measured by market reaction, transaction volume, and diversity of users. Still, net flows into TC contracts recover to and surpass pre-announcement levels for most pools, supporting viability of TC. Evidence on cooperation at the settlement layer is mixed: the aggregate share of non-cooperative blocks increases over time, but a shrinking number of actors process Tornado Cash transactions, indicating a fragility to the sustainability of censorship-resistance. Non-cooperation is not explained by tokenomics, and changes in perception around legal authority and clarity of regulation appears to be a key factor for whether to cooperate.
Keywords: G18; G28; G29; D40; F51; O30; 330; decentralized systems; digital assets; privacy; regulation; sanctions